2006
DOI: 10.1111/j.1445-2197.2006.03715.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of a Contemporary Amputation Series

Abstract: This series agrees with the current published work in finding that patients undergoing major lower limb amputation are older, with a high prevalence of comorbid conditions. Successful prosthesis rehabilitation depends on patient selection and a multidisciplinary approach. Despite a low immediate mortality, the overall long-term results of lower limb amputation remain dismal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
104
7
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(146 citation statements)
references
References 19 publications
23
104
7
5
Order By: Relevance
“…LLA is often performed as a life-saving measure for a critically ischemic or infected limb in patients with DM or PVD. 1,26) These critically ill patients may not survive the perioperative period. Additionally, unresolved underlying diseases may disturb wound healing and cause recurrent infections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LLA is often performed as a life-saving measure for a critically ischemic or infected limb in patients with DM or PVD. 1,26) These critically ill patients may not survive the perioperative period. Additionally, unresolved underlying diseases may disturb wound healing and cause recurrent infections.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, PVD and DM accounted for 61.0%-92.5% of LLAs. [1][2][3][4] Previous studies have also reported high postoperative mortality rates ranging from 4.2% to 13.5% among patients undergoing LLA. 2,3,[5][6][7][8][9][10][11][12] Reported risk factors for death after LLA include age; male sex; the site of amputation; the requirement of dialysis; and a diagnosis of PVD, DM, coronary artery disease, myocardial infarction, or renal insufficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was not possible to determine the reasons for death in our database, but previous studies have reported a 6%-10% 30-day mortality in this patient population. [19][20][21] Mortality among lower-extremity amputees has been shown to increase with the degree of renal dysfunction and is greatest in dialysis-dependent patients, who have a reported 30-day mortality of 16%. 22 Patients with diabetes have also been shown to have twice the risk of postoperative mortality after lower-extremity amputation compared with nondiabetic patients.…”
Section: Mortalitymentioning
confidence: 99%
“…2 Outcome in rehabilitation is also influenced by psychological and cognitive wellbeing of an individual, social support, economic status and multiple prosthesis related factors. 3,4 After lower limb amputation, the main aim of the rehabilitation team is to restore mobility and optimum physical functioning of an individual.…”
Section: Introductionmentioning
confidence: 99%